Playing Together: Analyzing Jazz Improvisation to Improve the Multiframe. Issue 1 (2nd June 2016) - Powers, Zach; Grimm, Stephanie
Abstract : Musical terminology is often used when discussing narrative forms of art. However, this is seldom accompanied by a systematic application of musical concepts for use by artists in these other mediums. Comics, in particular, parallel music in terms of the multiframe, where various individual elements are perceived at once. Therefore, a useful analogy can be made between the multiframe and thematic and vertical musical construction. The interactivity among jazz musicians during a collective improvisation exemplifies this musical simultaneity, and this article creates an analogy between improvisation and narrative comics, deriving several analytical tools that can be used to inform the creation of more meaningful multiframes.